Kajian Daya Saing Tenaga Kerja Lokal Di Kabupaten Kutai Kartanegara - Heru Suprapto; Sugeng Raharjo (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2017)
The competitiveness of local labor is the ability of local workers compared to migrant workers. Data analysis consisted of three activity flow which happened collectively that is data collecting, data reduction, data presentation, conclusion / verification. The results show that in positions top and midle management are mostly filled by migrant workers, while low management is mostly filled by local labor. On competitiveness indicator is obtained a description of the advantages as well as weakness of local workforce compared with migrant workers.Keywords : Local labor, Competitiveness